Leaching mechanism of semiconducting minerals a historical note - Habashi F. (Journal of Mining and Metallurgy. Section B: Metallurgy)
mechanism of leaching of semiconducting minerals such as CuS, ZnS, UO2, etc., has been the subject of intensive speculation by hydrometallurgy researchers in the early 1950s who assumed the formation of intermediate surface complexes that could be neither separated nor identified by physico-chemical techniques. The electrochemical theory of leaching introduced in the late 1960s resolved this problem by comparing the leaching process to a corrosion phenomenon similar to the corrosion of metals. A historical summary of these proposals is presented.